Press Items on 27 May, 1957 - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Survey of Hungarian press on several topics including freedom of religion; Anna Kéthly; labor code revision; the journalists' union; lay-offs; party conference; István Dobi's telegram to Tito on 24 May, 1957.